A Survey of Multilevel Voltage Source Inverter Topologies, Controls, and Applications - Ibrahim Haruna Shanono; Nor Rul Hasma Abdullah; Aisha Muhammad (Institute of Advanced Engineering and Science, 2018)
Multi-level converters are every day attracting research interest due to it tremendous positive contributions they are making in the power industries. The converter has put hope in the minds of power electronic engineers that a time will come when it will break a record by providing an efficient means of utilizing the abundant renewable energy resources. The paper presents a review of multilevel voltage source converters that are widely being used in engineering applications. It reports the technological advancements in converter topologies of Flying Capacitor (FC), Neutral Point (NPC) /Diode Clamped, and Cascaded H-Bridge (CHB) with their respective advantages and disadvantages. Recent customized/hybrid topologies of the three-phase multilevel inverter with reduced component count and switching combination are reported. The paper also reviewed different modulation techniques such as the multilevel converter carrier base PWM, Space Vector Modulation techniques (SVM), and Selective Harmonic Elimination method (SHE-PWM). Finally, various multilevel converters areas of application were highlighted. This review will expose the reader to the latest developments made in the multi-level topologies, modulation techniques, and applications.